2017
DOI: 10.1111/jpi.12389
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin alleviates cadmium‐induced liver injury by inhibiting the TXNIP‐NLRP3 inflammasome

Abstract: Cadmium (Cd) is a persistent environmental and occupational contaminant that accumulates in the liver and induces oxidative stress and inflammation. Melatonin possesses potent hepatoprotective properties against the development and progression of acute and chronic liver injury. Nevertheless, the molecular mechanism underlying the protective effects of melatonin against Cd-induced hepatotoxicity remains obscure. In this study, we aimed to investigate the effects of melatonin on Cd-induced liver inflammation and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
103
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 172 publications
(109 citation statements)
references
References 58 publications
(108 reference statements)
6
103
0
Order By: Relevance
“…These effects of melatonin against sepsis in mice lead to an increased survival rate of animals . The beneficial effects due the inhibition of the NLRP3 inflammasome by melatonin are receiving increased attention because it is related to the improvement of diseases such as cadmium‐induced liver injury, acute lung injury, and subarachnoid hemorrhage‐induced brain injury . However, the specific interaction of melatonin with the NLRP3 inflammasome during sepsis in cardiac tissue remains to be identified.…”
Section: Discussionmentioning
confidence: 99%
“…These effects of melatonin against sepsis in mice lead to an increased survival rate of animals . The beneficial effects due the inhibition of the NLRP3 inflammasome by melatonin are receiving increased attention because it is related to the improvement of diseases such as cadmium‐induced liver injury, acute lung injury, and subarachnoid hemorrhage‐induced brain injury . However, the specific interaction of melatonin with the NLRP3 inflammasome during sepsis in cardiac tissue remains to be identified.…”
Section: Discussionmentioning
confidence: 99%
“…Melatonin reduced liver injury and inflammation through decreasing serum ALT/AST levels, inhibiting pro-inflammatory cytokine production, preventing NOD-like receptor pyrin domain containing 3 (NLRP3) inflammasome activation, ameliorating oxidative stress, and attenuating hepatocyte death. In vivo and in vitro, Cd-induced TXNIP overexpression was markedly abrogated and the interaction between TXNIP and NLRP3 was decreased by melatonin [29]. In addition, melatonin increased hepatic GSH levels and improved histopathological changes after Cd 2+ exposure.…”
Section: Protective Effects Of Melatonin On Liver Injuriesmentioning
confidence: 99%
“…15,16 It was reported that the reduction in inflammasome activation could significantly decrease the level of inflammatory responses in neurons as a result of decreased caspase-1 activity and reduced production of IL-1. [20][21][22] In this study, we established a rat model of SCI and treated SCI rats with MT to explore the molecular mechanisms underlying the therapeutic effect of MT in the treatment of SCI. 18 Although the reduction in inflammatory responses is transient in nature, it can lead to significant improvements in terms of functional and histopathological properties of neurons.…”
mentioning
confidence: 99%